Ernst Feuereisen and Gordon Carruthers - 02 - (Author); (Interviewer); (Publisher) (1930)
Photograph - Ernst Feuereisen and Gordon Carruthers sitting on a boat with their catch, likely at Pelican Portage, Alberta